1998
DOI: 10.1097/00002030-199814000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the maternal–infant zidovudine regimen utilized in the Pediatric AIDS Clinical Trial Group 076 Study

Abstract: There were no identified problems that would alter current recommendations for the routine use of ZDV for the prevention of mother-child HIV-1 transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
6

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 13 publications
5
71
0
6
Order By: Relevance
“…It consisted of an antenatal treatment starting at 14 or 28 weeks gestation, continuing with intravenous intrapartum and then treatment of the neonate for six weeks. The results are similar to those initially reported in 1994; the estimated HIV transmission rate for infants who received the placebo was 22.6%, compared with 7.6% for those who received ZDV, giving a 66% reduction in risk of transmission [8].…”
Section: Mother-to-child Transmissionsupporting
confidence: 87%
See 2 more Smart Citations
“…It consisted of an antenatal treatment starting at 14 or 28 weeks gestation, continuing with intravenous intrapartum and then treatment of the neonate for six weeks. The results are similar to those initially reported in 1994; the estimated HIV transmission rate for infants who received the placebo was 22.6%, compared with 7.6% for those who received ZDV, giving a 66% reduction in risk of transmission [8].…”
Section: Mother-to-child Transmissionsupporting
confidence: 87%
“…In PACTG 076 exposed infants, observed mortality at 18 months was 1.4% in ZDV-exposed, compared to 3.5% in placebo infants [8]. In contrast, another clinical study made with 291 infants, 139 of which used ZDV, the rapid disease progression rate was 29.4% in the no ZDV group compared with 70.6% in the ZDV group (p=0.012).…”
Section: Rapid Disease Progression (Rdp)mentioning
confidence: 89%
See 1 more Smart Citation
“…Several concerns have been raised about the safety of ZDV treatment during pregnancy. First, as with all drugs taken during pregnancy, the potential for teratogenesis must be considered; however, the incidence of birth defects in ZDV-exposed children does not seem to be increased, 5,16 and the ZDV regimen in our trial began after completion of organogenesis. Second, ZDV can be integrated into infant DNA, and animal data suggest the possibility that in utero ZDV exposure can cause tumors.…”
Section: Discussionmentioning
confidence: 96%
“…The only short-term adverse event in children attributed to ZDV in this study was mild anemia that resolved rapidly without intervention. 4,5 Moreover, after an additional 4 years of follow-up of 122 ZDV-exposed children in this trial, no additional adverse events clearly associated with ZDV treatment were identified. 6 Nonetheless, concerns have been raised that prenatal ZDV exposure may cause cancer, mitochondrial toxicity, or other problems.…”
mentioning
confidence: 76%